2017
DOI: 10.3389/fpsyg.2017.00650
|View full text |Cite
|
Sign up to set email alerts
|

Long-Time Exposure to Violent Video Games Does Not Show Desensitization on Empathy for Pain: An fMRI Study

Abstract: As a typical form of empathy, empathy for pain refers to the perception and appraisal of others’ pain, as well as the corresponding affective responses. Numerous studies investigated the factors affecting the empathy for pain, in which the exposure to violent video games (VVGs) could change players’ empathic responses to painful situations. However, it remains unclear whether exposure to VVG influences the empathy for pain. In the present study, in terms of the exposure experience to VVG, two groups of partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 87 publications
(111 reference statements)
4
18
1
1
Order By: Relevance
“…A possible interpretation of the findings of the present study is that the others' representation perceived during fighting activities (kill enemies) is in contrast with the representation of the others experienced during social involvement. The discrepancy between these findings and those discussed above of recent studies that did not report a neurobiological desensitization (Szycik, et al 2017b;Gao et al, 2017) could be explained by the different stimuli used among the studies. In fact, in those previous studies the neurobiological activation were evaluated in response to stimuli designed to elicit empathic reactions to pain.…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…A possible interpretation of the findings of the present study is that the others' representation perceived during fighting activities (kill enemies) is in contrast with the representation of the others experienced during social involvement. The discrepancy between these findings and those discussed above of recent studies that did not report a neurobiological desensitization (Szycik, et al 2017b;Gao et al, 2017) could be explained by the different stimuli used among the studies. In fact, in those previous studies the neurobiological activation were evaluated in response to stimuli designed to elicit empathic reactions to pain.…”
Section: Discussioncontrasting
confidence: 95%
“…As suggested by Siegal and Varley (2002), the amygdala is a core structure for the comprehension of others' thoughts and emotions. Conversely, studies on long-term effects of the exposure to violent video games reported different results (Szycik et al, 2017a(Szycik et al, , 2017bGao et al, 2017), where habitual use of violent video game in chronic players did not produce any effect on brain activity in response to emotional stimuli compared to nonchronic players. These studies sustain that the violent contents in video games do not have long-term influence on brain activity, emotional processing, or aggressive behaviours but only possible short-term effects immediately after or during the exposure to violent video games (Szycik et al, 2017a(Szycik et al, , 2017b.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, past research has focused primarily on a single factor affecting the player and failed to conduct a more comprehensive investigation, such as the interaction of two factors. Further, there is debate about the relationship between violent video games and empathy and aggression ( Gao et al, 2017 ; Hilgard et al, 2017 ; Kepes et al, 2017 ; Szycik et al, 2017 ). To remedy this deficiency, the present study investigates the influence of the moral attributes of game characters and that of empathy in the players, as well as their interactive effect.…”
Section: Introductionmentioning
confidence: 99%